2013
DOI: 10.1073/pnas.1219982110
|View full text |Cite
|
Sign up to set email alerts
|

Flagella stator homologs function as motors for myxobacterial gliding motility by moving in helical trajectories

Abstract: Significance Gliding is a form of enigmatic bacterial surface motility that does not use visible external structures such as flagella or pili. This study characterizes the single-molecule dynamics of the Myxococcus xanthus gliding motor protein AglR, a homolog of the Escherichia coli flagella stator protein MotA. However, the Myxococcus motors, unlike flagella stators, lack peptidoglycan-binding domains. With photoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
157
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(162 citation statements)
references
References 28 publications
2
157
0
Order By: Relevance
“…Genomic analysis has shown that the M. xanthus motor complexes, unlike the MotAB complexes of enteric bacteria, lack peptidoglycan-binding domains and thus are free to move within the membrane (7). Consistent with this idea, the motor protein AglR and the motor-associated protein AgmU (GltD) have been observed to decorate a helical macrostructure that rotates as cells move forward (7,8). In addition, tracking the movements of single AglR molecules using single-particle photoactivatable localization microscopy (sptPALM) (22) revealed that the gliding motors containing AglR molecules move in helical trajectories.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Genomic analysis has shown that the M. xanthus motor complexes, unlike the MotAB complexes of enteric bacteria, lack peptidoglycan-binding domains and thus are free to move within the membrane (7). Consistent with this idea, the motor protein AglR and the motor-associated protein AgmU (GltD) have been observed to decorate a helical macrostructure that rotates as cells move forward (7,8). In addition, tracking the movements of single AglR molecules using single-particle photoactivatable localization microscopy (sptPALM) (22) revealed that the gliding motors containing AglR molecules move in helical trajectories.…”
mentioning
confidence: 78%
“…1A) (7). This model explains evenly distributed traffic jam sites in gliding cells, without invoking that force is transmitted to the surface by breaching the peptidoglycan barrier (21,23); however, how the bidirectional motion of gliding motors generates unidirectional cell movements remains unknown.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations